TIBETAN MEDICINE - Rao, S. K. Ramachandra (Medknow Publications & Media Pvt Ltd, 1982)
This paper explains Tibetan Medicine and its adherence to the tradition. The author has also analysed its historicalbackground and its relationship to Ayurveda.